Pengaruh Leverage dan Ukuran Perusahaan Terhadap Profitabilitas Dengan Modal Intelektual sebagai Pemoderasi - Andreani, Ni Luh Meili; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2019)
This study aims to analyze the effect of leverage and firm size on profitability with intellectual capital as a moderator. This research was conducted on textile and garment sub-sector companies listed on the Indonesia Stock Exchange in 2015-2017. Samples were taken using saturated sampling techniques, so the entire population was sampled as many as 11 companies. There were 33 samples from three years of research observations. The results show that leverage has a negative effect on profitability. This shows that the use of debt will risk the occurrence of financial difficulties. Intellectual capital weakens the influence of leverage on profitability. This shows that the company must pay attention to resource management, namely increasing competence, ability, skills (knowledge) and knowledge of employees will contribute to debt management so as to increase the profitability of the company.  Keywords : Intellectual capital, leverage, company size, profitability.